Etodolac Thiosemicarbazides: A novel class of hepatitis C virus NS5B polymerase inhibitors - (:unkn) unknown (My University, 2013)
A novel series of new etodolac hydrazide derivatives, 1-2-(1,8-diethyl-1,3,4,9-tetrahydropyrano3,4-b]indole-1-yl)acetyl]-4-alkyl/aryl thiosemicarbazides 3a-h] have been synthesized in this study. The structures of the new compounds were determined by spectral (FT-IR, 1H-NMR, 13C-NMR and LC-MS) methods. Inhibition of hepatitis C virus NS5B RNA dependent RNA polymerase activity by etodolac thiosemicarbazides was evaluated in vitro by primer dependent elongation assays. The most active compounds of this series were 3a (SGK 224), 3d (SGK 227) and 3e (SGK 229) with IC50 values of 18.7 μM, 29.2 μM and 16.8 μM, respectively. Binding mode investigations of the most active compound 1-2-(1,8-diethyl-1,3,4,9-tetrahydropyrano3,4-b]indole-1-yl)acetyl]-4-allyl thiosemicarbazide (3e) suggested that TP-II of HCV NS5B polymerase may be the potential binding site for etodolac thiosemicarbazides and provided clues for modifications to improve the potency of etodolac derivatives.
Keywords: etodolac; Hepatit C NS5B polymerase; pyrano3,4-b]indole; thiosemicarbazide